2022
DOI: 10.3390/ijerph19084590
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and COVID-19 Related Anxiety among Malaysian Women during the COVID-19 Pandemic

Abstract: The combination of COVID-19 outbreaks and nationwide lockdown led to an increased prevalence of psychological distress among the population, especially women, as they have to cope with greater family and work demands. We aimed to identify the factors contributing to psychological distress among Malaysian women during the COVID-19 pandemic. A cross-sectional study was conducted between October 2020 and April 2021, in a teaching hospital in Kuala Lumpur, Malaysia. A self-administered questionnaire was distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Abdul Latif et al conducted a study on the population of 350 Malaysian women between October 2020 and April 2021 and revealed that low education level unemployment and loss of income were significantly associated with a higher psychological burden [60]. Bussè et al also confirmed that long-term higher depression was predicted by a model built on baseline information where having lower education was a significant predictor [50].…”
Section: Factors Associated With Poor Mental Health Outcomes (Severe ...mentioning
confidence: 97%
“…Abdul Latif et al conducted a study on the population of 350 Malaysian women between October 2020 and April 2021 and revealed that low education level unemployment and loss of income were significantly associated with a higher psychological burden [60]. Bussè et al also confirmed that long-term higher depression was predicted by a model built on baseline information where having lower education was a significant predictor [50].…”
Section: Factors Associated With Poor Mental Health Outcomes (Severe ...mentioning
confidence: 97%
“…This topic is therefore both current and of great social impact considering that both physical and psychological manifestations related to COVID-19 have been identified, which can persist long-term even beyond recovery [ 172 ]. In fact, several authors around the world have also reported symptoms of psychological stress such as: sleep loss, nervousness, fatigue, depression, anxiety, [ 173 , 174 , 175 , 176 , 177 ] especially in the female population, very often linked to other cofactors such as the social and economic status or the patient’s health. Fortunately, these are often of a transitory type, especially if considered short-term [ 178 ], but, in the literature, there are several manuscripts that [ 172 , 179 , 180 , 181 , 182 , 183 ] report an up to three times increased risk in women of experiencing long-term symptoms.…”
Section: Discussion and Potential Future Approachesmentioning
confidence: 99%
“…Student [23] Marital status [25] Family size [25] Living arrangement [32] Internet access [35] Hospital admission for surgical procedure [26] Internet addiction [37] Privacy in home [29] Exercise [29] Social support [30] [25]…”
Section: Social Factorsmentioning
confidence: 99%